Seroprevalence of SARS-Cov-2 in the setting of a non-dedicated COVID-19 hospital in a low CoV-2 incidence area: Implications for surgery. (December 2020) - Medas, Fabio; Cappellacci, Federico; Anedda, Giacomo; Canu, Gian Luigi; Del Giacco, Stefano; Calò, Pietro Giorgio; Firinu, Davide
Abstract: The aim of this study was to assess the seroprevalence of SARS-Cov-2 in the setting of a non-dedicated COVID-19 hospital in a low CoV-2 incidence area. We analysed the data of the patients admitted at our surgical department during the period 31st March - June 30, 2020. Among 86 patients included in the study, we found 2 (2.3%) patients positive for both SARS-CoV-2 specific IgM and IgG, 2 (2.3%) for only SARS-CoV-2 specific IgM, and 1 for only SARS-CoV-2 specific IgG. Thus, seroprevalence for SARS-CoV-2 was 5.8%; nasopharyngeal swab was negative in all the cases. Considering the current limitations in sensitivity of nasopharyngeal swab, the uncertainty in the natural history of SARS-CoV2, and the reported prevalence of CoV-2, we think that careful preadmission triage and tests, the use of personal protective equipment and safe management of surgical smoke are mandatory also in our context of low CoV-2 incidence area.